Isolation and characterization of bacterium producing lipid from short-chain fatty acids. (February 2016) - Okamura, Yoshiko; Nakai, Shota; Ohkawachi, Masahiko; Suemitsu, Masahiro; Takahashi, Hirokazu; Aki, Tsunehiro; Matsumura, Yukihiko; Tajima, Takahisa; Nakashimada, Yutaka; Matsumoto, Mitsufumi
Highlights: Propionic acid-assimilating bacteria were obtained from marine gravel sample. Nitratireductor sp. OM-1 can assimilate VFAs ranging from C2 to C5 and glycerol. This strain produces triacylglycerol under the acetic acid–propionic acid conditions. This strain produces 2-butenoic acid 1-methylethyl ester when depleted nitrogen. This strain has the potential of activated sludge reduction and biodiesel production. Abstract: Anaerobic fermentation generates propionic acid, which inhibits microbial growth and accumulates in wastewater containing increased amounts of organic matter. We therefore isolated a propionic acid-assimilating bacterium that could produce triacylglycerol, for use in wastewater treatment. Nitratireductor sp. strain OM-1 can proliferate in medium containing propionic, acetic, butyric, and valeric acids as well as glycerol, and produces triacylglycerol when both propionic and acetic acids or glycerol are present. In composite model wastewater containing acetic acid, propionic acid and glycerol, this strain shows an even higher conversion rate, suggesting that it is suitable for wastewater treatment. Further, nitrogen depletion in medium containing an acetic–propionic acid mixture resulted in the production of the light oil 2-butenoic acid 1-methylethyl ester, but not triacylglycerol. Collectively, our data indicate that strain OM-1 has the potential to reduce accumulation of activated sludge in wastewater treatment and may contribute to the production of biodiesel.